Coaching with Distinctive Human Strengths for Intentional Change - Dyck, Loren R. (Journal of Leadership, Accountability and Ethics, 2017)
This paper describes and asserts the positive influence of coaching with distinctive human strengths for the intentional change of the coachee. Intentional Change Theory is introduced as the conceptual backdrop to discuss human strengths and to contrast two approaches to connect the real self and the ideal self. The Balanced Attributes Model (BAM) and Distinctive Strengths Model (DSM) represent different assumptions, values, and perspectives on intentional change. I use the DSM as the foundation for three examples of how a coach could work with coachees to pursue their respective intentional change.